Self-initiated expatriation: Career experiences, processes and outcomes - Doherty, N.; Richardson, Julia; Thorn, K. (Emerald Group Publishing Ltd., 2013)
Purpose – This special issue seeks to scope the past, present and future study of those individuals who independently journey abroad for work – the self-initiated expatriate – a topic which is now attracting increasing attention among management scholars and practitioners alike. Design/methodology/approach – This introductory paper takes the form of a brief commentary of the development of the field and a synthesis of the papers in this special edition. Findings – Beginning in the late 1990s with a slow trickle of papers exploring the experiences of individuals who had initiated their own expatriation, our understanding of self-initiated expatriates (SIEs) and self-initiated expatriation (SIE) has developed exponentially. This development has given rise to a growing awareness of this form of mobility as a potentially powerful force in the increasingly varied global labour market. Yet, as this special issue will argue, there is still a range of conceptual, theoretical and empirical challenges in the study of SIEs, not least of which is a lack of clarity in how the term is used and understood. Despite the expansion of the field, it has hitherto focused primarily on the experiences of professional SIEs moving from and between developed countries. The papers in this issue therefore, address the need for both greater conceptual clarity and for greater empirical diversity. Originality/value – The papers included in this special issue each address fundamental issues in the study of the SIE population. Purpose – This special issue seeks to scope the past, present and future study of those individuals who independently journey abroad for work – the self-initiated expatriate – a topic which is now attracting increasing attention among management scholars and practitioners alike. Design/methodology/approach – This introductory paper takes the form of a brief commentary of the development of the field and a synthesis of the papers in this special edition. Findings – Beginning in the late 1990s with a slow trickle of papers exploring the experiences of individuals who had initiated their own expatriation, our understanding of self-initiated expatriates (SIEs) and self-initiated expatriation (SIE) has developed exponentially. This development has given rise to a growing awareness of this form of mobility as a potentially powerful force in the increasingly varied global labour market. Yet, as this special issue will argue, there is still a range of conceptual, theoretical and empirical challenges in the study of SIEs, not least of which is a lack of clarity in how the term is used and understood. Despite the expansion of the field, it has hitherto focused primarily on the experiences of professional SIEs moving from and between developed countries. The papers in this issue therefore, address the need for both greater conceptual clarity and for greater empirical diversity. Originality/value – The papers included in this special issue each address fundamental issues in the study of the SIE population and offer perspectives that further our understanding of this group and their experiences.